2015
DOI: 10.4067/s0718-58392015000500013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding bulking materials over the composting process of municipal solid biowastes

Abstract: Biowastes (BW), the main raw materials for the composting installations in developing countries, are characterized for containing uncooked food wastes (FW), high moisture content, low porosity, acidic pH, and low C/N ratios which affects the overall composting process (CP). In this study, we evaluated the effect of adding sugarcane bagasse (SCB) and star grass (SG) (Cynodon plectostachyus (K. Schum.) Pilg.) as bulking materials (BM) over the quality of the substrate, progress of the process, and quality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
3
0
4
Order By: Relevance
“…Efikasnost procesa kompostiranja zavisi od velikog broja faktora, a najvažniji od njih su: odnos ugljenika i azota, veličina čestica, temperatura, koncentracija kiseonika, nivo vlažnosti i pH vrednost [7].…”
Section: Faktori Koji Utiču Na Proces Kompostiranjaunclassified
“…Efikasnost procesa kompostiranja zavisi od velikog broja faktora, a najvažniji od njih su: odnos ugljenika i azota, veličina čestica, temperatura, koncentracija kiseonika, nivo vlažnosti i pH vrednost [7].…”
Section: Faktori Koji Utiču Na Proces Kompostiranjaunclassified
“…It is demonstrated that bulking agents speed up the degradation process at the initial stage of composting process and reduce the duration of composting [81]. The addition of bulking materials helps to achieve the thermophilic phase and lower the period of mesophilic phase [81,82]. The efficiency of composting process depends on Bulk Density, CEC and moisture holding capacity of the bulking material added.…”
Section: Termite Mound Soil As a Bulking Materials In Compostingmentioning
confidence: 99%
“…En todos los experimentos, la mayor reducción en el contenido de SV se observó durante la fase termofílica (ver Figura 1b), que está de acuerdo con la rápida descomposición de compuestos fácilmente degradables como carbohidratos, proteínas que son usados como fuente de energía y nitrógeno por los consorcios microbianos (Jiang-ming, 2017;Hemidat et al, 2018;Waqas et al, 2018). Entre los tratamientos evaluados, la máxima reducción de SV se presentó en A2 y A3, los cuales consistentemente presentaron las mayores temperaturas medias durante el proceso indicando una mayor actividad microbiológica, que pudo estar favorecida por el incremento en la disponibilidad de oxígeno asociada a la porosidad aportada por el PE (Oviedo et al, 2015). En contraste, las menores pendientes de biodegradación se observaron en los tratamientos A0 y A1, los cuales no mostraron diferencias significativas (p>0.05).…”
Section: Degradación De La Materia Orgánica Durante El Procesounclassified